Formação de professores para educação musical: base de conhecimento necessária para a docência on-line - Colabardini, Júlio César de Melo (Universidade Federal de São Carlos, 2015)
This work focuses on teacher learning and new knowledge towards the use of digital technology resources and its relation to the professional development of teachers working in Music Education courses Distance. The guiding questions were: What skills are required for teacher training in music education to work with digital technology resources, particularly in Distance Education? How these new learnings contribute to the professional development of teachers? The justification of this research permeates the relevance and topicality of the subject and deployment, relatively recent, the first three graduate courses in Brazil Music taught in distance education mode - UFSCar, UNB and UFRGS - observed the need for discussion of different aspects of the area of Musical Distance Education, especially the discussion on teacher training and educational alternatives in teaching in these institutions. Regarding the methodological procedures was followed a qualitative, descriptive and analytical approach. The study gathered six active teachers in Undergraduate Music courses in distance education mode, three of UNB and three UFSCar. Questionnaires were applied online, formed of objective and essay questions. The questionnaire was also used to select the subjects that were interviewed. The interviews were conducted online, focusing on the deepening of the data and filling gaps left by the questionnaire. The theoretical framework used in this work include the following topics: Distance Education, Teacher Training, Technology and Music Education. To guide and organize the development of this research this study was organized into four chapters: 1. Considerations training possibilities in contemporary society, TDIC and Music Technology. 2. Teacher Training and Distance Education. 3. methodological research course. 4. Analysis of the data. Finally, the conclusion, resumed the guiding questions of this work and the main elements of this work, looking for answers and highlighting certain aspects the light of the theoretical framework presented, finally seeking the completion of this work.
Keywords: Educação musical; Professores - formação; Educação a distância; Music education; Distance education; Teacher education; CIENCIAS HUMANAS::EDUCACAO